The transition to a circular economy: different paths for international and non-international micro-manufacturing firms - Tarlan Ahmadov; Samuel Foli; Susanne Durst; Wolfgang Gerstlberger (Discover Sustainability, 2024)
Abstract This article examines how environmental awareness, stakeholder pressure, circular economy orientation and internal barriers influence circular economy practices in international and non-international micro-firms. For this, we utilised fuzzy set qualitative comparative analysis (fsQCA) using data from 128 micro firms operating in different manufacturing industries in Estonia. Three paths were identified for explaining circular economy practices in internationally operating micro-firms and two paths for explaining it in micro-firms that do not operate internationally. Our results show that understanding the impact of the four before-mentioned aspects can be beneficial for engaging in circular economy efforts in both international and non-international micro-firms. The intricate five pathways (three for international and two for non-international) through which environmental awareness, stakeholder pressure, circular economy orientation, and internal barriers shape circular economy practices in micro-firms, challenging conventional understandings and offering nuanced insights for effective engagement in sustainable business practices. Based on the findings, theoretical and practical implications of this study and directions for future research are discussed.